Restructuration of architectural practice in integrated project delivery (IPD): two case studies. Issue 1 (18th February 2019) - Abdirad, Hamid; Dossick, Carrie S.
Abstract : Purpose: The purpose of this paper is to clarify that while integrated project delivery (IPD) methods can be momenta for restructuring architectural practice, they do not predetermine specific patterns of restructuration for the roles, responsibilities and services of architects. Design/methodology/approach: This paper is based on a multiple case study design; two IPD projects were theoretically sampled and studied. The data collection methods included semi-structured interviews and observations. An inductive data analysis approach was applied to frame the phenomena, conduct cross-case comparisons and develop propositions. Findings: While IPD implementations set expectations for new structures for practices, it is the project participants' situated decisions that lead to the restructuration of some dimensions of architectural practice. The dimensions in this study included team formation, design leadership and collaboration and architectural services. IPD project participants locally changed and redefined conventional roles, responsibilities and project artifacts (e.g. drawings and models) that concerned design development and coordination. Practical implications: IPD context, by itself, does not predetermine a fixed pattern of change in establishing designers' roles, responsibilities and services because restructuration is highly negotiated amongst the IPD parties and can lead to different responses to this contractual setting. Contracts set expectations for collaborative behavior, but the fulfillment of these expectations is situated and emerging as project participants negotiate to develop practices. Originality/value: While IPD research and guidelines aim to provide recipes for IPD implementation, this study contributes to the body of knowledge by clarifying that IPD is a context in which unprecedented ways of practice restructuration could emerge.